Analisis Stakeholder Dan Pengembangan Kemitraan Pendidikan Islam di MAN 1 Merangin - Ahmad Fauzi; Muhammad Aminullah; Yalhadi; Saidi Muzakir; Nuraini Arifah Fitriani (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze the role of stakeholders and the development of Islamic education partnerships in improving the quality of education at MAN 1 Merangin. This study used a descriptive approach supported by quantitative data from respondents consisting of students’ parents, teachers, school committee members, and other stakeholders. Data were collected through questionnaires, interviews, observation, and documentation. The data were analyzed through validity testing, reliability testing, normality testing, heteroscedasticity testing, simple linear regression, and the coefficient of determination. The results show that the research instruments were valid and reliable. The stakeholder partnership variable had a positive and significant effect on education quality, with a regression coefficient of 0.653 and a significance value of 0.000. The R Square value of 0.347 indicates that stakeholder partnerships contributed 34.7% to education quality. The findings also show that stakeholders’ perceptions of educational services were in the fairly good category. The school-parent relationship strategy was dominated by routine communication, parent meetings, involvement in school activities, and educational consultation. Support from the business sector and Corporate Social Responsibility programs also contributed to improving education quality through facilities assistance, educational activities, training programs, and scholarships. This study confirms that the development of Islamic education partnerships requires open communication, active participation, resource support, shared commitment, and continuous evaluation so that the quality of madrasah education can improve systematically and sustainably.